(untitled) (American Journal of Pedagogical and Educational Research, 2024)
In this article, in the process of preparing students of higher education institutions for constructive activity, the possibilities of developing a model of person-oriented relations, acquiring methodological tools, understanding, accepting and implementing a humanitarian position have been revealed.